Mempelajari Pengaruh Suhu dan Jenis Jeroan terhadap Mutu Tepung Jeroan - Tamrin, Tamrin; Putri, Cahyani Cahyanti; Rahmawati, Winda; Kuncoro, Sapto (abe.fp.unila.ac.id, 2023)
Animal feed with high protein content is currently difficult to obtain and has a relatively expensive price, so that the nutritional needs of livestock are less fulfilled. Therefore, this research was done to get livestock feed with good characteristics and to get information on the utilization of chicken organ meats to substitute fish flour in animal feed formulations of fish and poultry.The aim of the study was to study the temperature effect of 50oC, 70oC and 90oC and effectthe type of innards to the final water content, protein and color. Discover the highest protein content of intestinal starch, gizzard and chicken liver after the drying phase with 3 temperature parameters that is 50oC, 70oC, and 90oC. The research stage was carried out with the process of cleaning innards, cutting samples with a thickness of 0.2 cm for the liver and gizzard and a length of 5 cm for the intestine. The next process is drying, then measuring water content, grinding using a blender, sifting using a mesh 50 sieve, then a protein analysis is performed. The parameters observed in this research are moisture content, protein and color250 gram samples of wet innards can produce the average weight of chicken offal flour at all drying temperatures of 30.17 grams and can produce a yield value of 12.06%. The optimum temperature needed for the chicken offal drying process is at a temperature of 90 C with the old drying for 12 hours. The type of chicken innards (intestines, liver and gizzard) does not affect the water content in the end also protein but affects the color of chicken innards. The highest protein innards in the temperature of 90 C, has a percentage of protein in the intestines of 69.8%, liver 70.1%, and angizzard of 71.6%. Keywords: Chicken Innards, Color, Offal Flour, Protein, Temperature.